Telephone Operator Service Communication (Front Office) with Major Departments Regarding Guest Requests at Gumaya Tower Hotel Semarang - Laura Aviana Christie; Cindy Citya Dima (FKIP, Universitas Palangka Raya, 2023)
This final project aims to explain about Telephone Operator Service Communication (Front Office) with Major Departments Regarding Guest Requests at Gumaya Tower Hotel Semarang. Communication that is not going well, such as the absence of confirmation from between major departments, can make service less than optimal, causing guest complaints to occur. The data collection method used in this research is descriptive qualitative using observation data collection techniques, literature study and documentation in order to obtain accurate data regarding efforts to improve service to hotel guests. The research results that can be obtained from this study are that communication between major departments is very important in improving service to hotel guests. Telephone Operators also have a very important role in handling guest requests so that when guests need assistance and have requests telephone operators can help as much as possible so that guests feel satisfied. However, if the communication between the telephone operator and the relevant major departments does not go well, this can cause guest complaints. Good communication between the Telephone Operator (Front Office) and the major departments at Gumaya Tower Hotel Semarang can create good service and image for the hotel and can increase guest satisfaction.